2013
DOI: 10.1111/jfb.12027
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA variability of the pipefish Syngnathus abaster

Abstract: This study provides data on the genetic structuring of the pipefish Syngnathus abaster in the western Mediterranean and Adriatic Seas. A total of 109 specimens were collected in brackish-water biotopes. The control region and three other regions of the mitochondrial genome were analysed. The most relevant result was the high genetic structuring found by Bayesian inference (BI), maximum likelihood (ML) and network analyses, which were consistent in showing three well-separated clusters of S. abaster populations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 107 publications
(151 reference statements)
1
11
0
Order By: Relevance
“…This is probably due to the absence of dispersal stages combined with the exclusively benthic adults; conversely, the potential for migration across stretches of sea allows a shallower structuring in A. fasciatus. A similar pattern of substantial isolation between populations occurring in different brackish-water bodies was retrieved in the pipefish Syngnathus abaster Risso, 1827, a species occurring mostly in brackishwater environments across the Mediterranean Sea and characterised by egg brooding in a ventral pouch and hatching of benthic juveniles (Sanna et al, 2013). However, unlike A. fasciatus, S. abaster shows as well a further structuring into three deeply divergent clades occurring in different areas of the Mediterranean Sea (Western Mediterranean, Tyrrhenian ?…”
Section: A Unique Phylogeographical Pattern Among Mediterranean Fishesmentioning
confidence: 54%
“…This is probably due to the absence of dispersal stages combined with the exclusively benthic adults; conversely, the potential for migration across stretches of sea allows a shallower structuring in A. fasciatus. A similar pattern of substantial isolation between populations occurring in different brackish-water bodies was retrieved in the pipefish Syngnathus abaster Risso, 1827, a species occurring mostly in brackishwater environments across the Mediterranean Sea and characterised by egg brooding in a ventral pouch and hatching of benthic juveniles (Sanna et al, 2013). However, unlike A. fasciatus, S. abaster shows as well a further structuring into three deeply divergent clades occurring in different areas of the Mediterranean Sea (Western Mediterranean, Tyrrhenian ?…”
Section: A Unique Phylogeographical Pattern Among Mediterranean Fishesmentioning
confidence: 54%
“…Several mechanisms may cause genetic differentiation between marine species populations such as vicariance processes, caused by historical barriers, oceanographic discontinuities, local adaptation, and limited dispersal capabilities (Palumbi, ). The spatially isolated nature of costal lagoons, at both present and past sea levels, may lead to significant population differentiation in allopatry, as highlighted by the studies of the Mediterranean goby Pomatoschistus tortonesei (Mejri et al, ), the pipefish Syngnathus abaster (Sanna et al, ), and the lagoonal sand smelt Atherina lagunae (Trabelsi et al, ). Previous studies of lagoon species were based mainly on few genetic markers, but our genome‐wide SNP analysis indicated that genetic differentiation between geographically isolated populations can be widespread across the genome and that many of the loci exhibit concordant genetic structure.…”
Section: Discussionmentioning
confidence: 99%
“…Other syngnathid species, however display different distributions of genetic diversity, so species-specific characteristics need to be discerned and taken into account in management. The Mediterranean lagoon-dwelling pipefish Syngnathus abaster has a more complex haplotype network but no shared haplotypes between populations, and similar nucleotide diversity to seahorses (Sanna et al 2013), suggesting that the fragmented habitat and life history characteristics of the species have resulted in population isolation and breakdown of gene flow following the initial post-glacial expansion. One a larger geographical scale the seahorse H. erectus also demonstrates regionality and genomic divergence, with little connectivity between northern and southern populations occupying waters with very different environmental conditions (Boehm et al 2015).…”
Section: Genetic Variabilitymentioning
confidence: 99%
“…A single recent study has assessed genetic variation in H. guttulatus across a small part of the species' geographic range (NW Iberian Peninsula), and found no significant barriers to gene flow (Lopez et al 2015), but studies of three other syngnathid species from areas more representative of the geographic range of H. guttulatus suggest more defined population differentiation in such species. Contemporary population structure of the pipefish Syngnathus typhle has been shown to be influenced by Pleistocene glaciations, with post glacial recolonisation effects evident in movement of the geographic range north and eastwards (Wilson & Eigenmann Veraguth 2010), whilst another pipefish (S. abaster) displays significant post-glacial fragmentation and differentiation (Sanna et al 2013). Similarly, both contemporary (i.e.…”
Section: Introductionmentioning
confidence: 99%